Learning Difficulties and Needs of Indonesian Language Proficiency Test Participants in Jambi Province - Ernanda Ernanda; Yusra Dewi; Rasdawita Rasdawita; Titin Sri Utami (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This This descriptive qualitative study aims to explore the listening difficulties experienced by participants in the Indonesian Language Proficiency Test (UKBI) in Jambi Province, as well as their learning needs. Data were collected through open-ended interviews with 68 participants who had taken the UKBI at the Jambi Provincial Language Canter, with 25 transcripts analysed in depth using a thematic analysis framework. The findings indicate that listening skills represent the primary challenge, involving multidimensional difficulties that encompass cognitive-affective processes (focusing attention and regulating anxiety), stimulus characteristics (audio speed, dialectal diversity, lexical complexity, and recording quality), and participant-contextual factors (language background and test environment conditions). A gap was revealed between the preparation undertaken by participants and their actual needs, with participants recommending the development of a preparation book that includes varied practice questions, detailed explanations, practical and concise materials, strategic tips, as well as digital and audio access. This study contributes to the development of a framework for exploring listening difficulties and provides practical implications for the development of UKBI preparation materials that are more responsive to the needs of participants in regions with high linguistic diversity.